Publisher Correction: Clonal evolution of acute myeloid leukemia revealed by high-throughput single-cell genomics - Kiyomi Morita (Nature Portfolio, 2020)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-020-19902-7